The Effect of Exenatide on Cardiovascular Risk Markers in Women With Polycystic Ovary Syndrome - Dawson, Alison J.; Sathyapalan, Thozhukat; Vince, Rebecca; Coady, Anne-Marie; Ajjan, Ramzi A.; Kilpatrick, Eric S.; Atkin, Stephen L. (Frontiers in Endocrinology, 2019)
Background: Polycystic ovary syndrome (PCOS) is associated with an adverse cardiovascular risk profile including a prothrombotic state. Exenatide has been shown to be effective at improving insulin sensitivity and weight loss in PCOS; therefore this study was undertaken to assess its effects on weight, endothelial function, inflammatory markers, and fibrin structure/function in overweight/obese women with PCOS. Methods: Thirty overweight/obese anovulatory women with all 3 Rotterdam criteria received exenatide 5mcg bd for 4 weeks then 10mcg bd for 12 weeks. The primary outcome was change in weight; secondary outcomes were changes in endothelial function (Reactive Hyperemia-Peripheral Arterial Tonometry (RH-PAT)), serum endothelial markers (ICAM-1, VCAM-1, E-selectin and P-selectin), change in inflammation (hsCRP), and alteration in clot structure and function (maximum absorbance (MA), and time from full clot formation to 50% lysis (LT)). Results: Twenty patients completed the study. Exenatide reduced weight 111.8±4.8kg to 108.6±4.6kg p=0.003. Serum endothelial markers changed with a reduction in ICAM (247.2±12.9 to 231.3±11.5ng/ml p=0.02), p-selectin (101.1±8.2 to 87.4±6.6 ng/ml p=0.01) and e-selectin (38.5±3.3 to 33.6±2.6 ng/ml p=0.03), without an overt change in endothelial function. Inflammation improved (CRP; 8.5±1.4 to 5.6±0.8 mmol/L p=0.001), there was a reduction in clot function (LT; 2987±494 to 1926±321s p=0.02) but not clot structure. Conclusion: Exenatide caused a 3% reduction in weight, improved serum markers of endothelial function, inflammation and clot function reflecting an improvement in cardiovascular risk indices in these women with PCOS. This suggests exenatide could be an effective treatment for obese women with PCOS.